CROHN’S DISEASE: CURRENT INSIGHTS INTO PATHOGENESIS, DIAGNOSIS AND TREATMENT - Weronika Radecka; Aleksandra Grygorowicz; Klaudia Baran; Michał Ględa; Michał Szyszka; Weronika Kozak; Agnieszka Szreiber; Karol Grela; Karolina Nowacka; Kamil Jabłoński; Anna Woźniak (International Journal of Innovative Technologies in Social Science, 2025)
Background: Crohn’s disease (CD) is a chronic, relapsing inflammatory bowel disease with rising global incidence and substantial long-term morbidity. Its heterogeneous clinical course reflects a complex interplay between genetic susceptibility, environmental factors, intestinal dysbiosis, epithelial barrier dysfunction, and dysregulated immune responses. Advances in diagnostics and therapeutics have transformed CD management, yet disease progression and complications remain common.Methods: This narrative review synthesizes current evidence on the pathophysiology, clinical presentation, diagnostic strategies, and treatment of Crohn’s disease. Peer-reviewed literature was examined focusing on genetic and immunological mechanisms, microbiome alterations, diagnostic modalities, conventional and advanced therapies, nutritional and surgical management, and emerging experimental approaches.Results: Crohn’s disease pathogenesis involves polygenic risk factors (e.g., NOD2, ATG16L1, IL23R), impaired autophagy, dysbiosis, and aberrant innate and adaptive immune activation. Diagnosis requires an integrated approach combining biomarkers, endoscopy with histology, and cross-sectional imaging. Therapeutic strategies have shifted toward a treat-to-target model, emphasizing mucosal healing through biologics, small-molecule agents, immunomodulators, and selected nutritional interventions. Novel microbiome and cell-based therapies show promise but remain investigational.Conclusion: Despite major therapeutic advances, Crohn’s disease continues to impose significant disease burden. Early diagnosis, proactive treatment, and personalized, mechanism-based strategies are essential to prevent cumulative bowel damage. Ongoing research into precision medicine and microbiome-targeted therapies may further improve long-term outcomes.